2011
DOI: 10.1111/j.1743-6109.2010.01961.x
|View full text |Cite
|
Sign up to set email alerts
|

The Serotonin Transporter Plays an Important Role in Male Sexual Behavior: A Study in Serotonin Transporter Knockout Rats

Abstract: Introduction Serotonin (5-HT) is an important neurotransmitter for sexual behaviors. Heterozygous (+/−) serotonin transporter (SERT) rats and SERT knockout rats (−/−) have serotonergic disturbances with significant elevations of basal extracellular 5-HT levels. Aim To investigate the putative role of the SERT in male sexual behavior. Methods After extensive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
58
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 60 publications
10
58
2
Order By: Relevance
“…This observation is in line with the finding that 5-HTT −/− mice displayed increased anxiety in the EPM and light/dark box only when exposed to predator odor (Adamec et al 2006). Finally, while prenatal fluoxetine did not alter sexual behavior, it was reduced in 5-HTT −/− rats, but only after extensive training (Chan et al 2010). The comparisons between the effects of pharmacological 5-HTT blockade and of lifetime 5-HTT absence suggest that 5-HT-induced neurodevelopmental changes, rather than lifetime effects, explain the observed phenotypes in 5-HTT −/− rodents.…”
Section: Discussionmentioning
confidence: 79%
“…This observation is in line with the finding that 5-HTT −/− mice displayed increased anxiety in the EPM and light/dark box only when exposed to predator odor (Adamec et al 2006). Finally, while prenatal fluoxetine did not alter sexual behavior, it was reduced in 5-HTT −/− rats, but only after extensive training (Chan et al 2010). The comparisons between the effects of pharmacological 5-HTT blockade and of lifetime 5-HTT absence suggest that 5-HT-induced neurodevelopmental changes, rather than lifetime effects, explain the observed phenotypes in 5-HTT −/− rodents.…”
Section: Discussionmentioning
confidence: 79%
“…This falls under the umbrella 'normal IELT and no control'. Classification of PE is still evolving as different classification models offer different clinical and research benefits [Cahangirov et al 2011;Chan et al 2011;Clément et al 2009;Waldinger and Olivier, 2005;Pattij et al 1995].…”
Section: Definition Of Premature Ejaculationmentioning
confidence: 99%
“…Both human and animal studies showed that serotonin plays an important role in sexual and particularly ejaculatory activity Waldinger, 2005;de Jong et al, 2006;Olivier et al, 2006;Chan et al, 2011). In some cases, a biologic variation in the IELT in men may be because of different regulation of the serotonergic receptor subtypes and/or to other genetic factors.…”
Section: Serotonin (5-ht)mentioning
confidence: 99%